Extramammary Paget Disease in the Peristomal Skin of an Ileal Conduit Reconstructed With a Pedicled Anterolateral Thigh Flap - Makoto Shibuya, MD; Kou Fujisawa, MD; Yuichiro Yokoyama, MD; Kazuto Sasaki, MD; Soichiro Ishihara, MD; Hiroyuki Abe, MD; Mutsumi Okazaki, MD (Plastic and Reconstructive Surgery, Global Open)
Summary:. An ileal conduit is the most commonly used urinary diversion following radical cystectomy. Malignancy of the ileal conduit rarely occurs, and Paget disease has not been reported in the peristomal skin of an ileal conduit. Herein, we describe a case of extramammary Paget disease in the peristomal skin of an ileal conduit. A 61-year-old male patient had undergone total pelvic exenteration along with ileostomy and ileal conduit diversion for colorectal cancer 30 years previously. The patient presented with a large skin ulcer around the ileal conduit in his right lower abdomen. The lesion, including the distal end of the ileal conduit, was excised based on a preoperative mapping biopsy, and the skin defect measuring 9 cm × 20 cm around the ileal conduit was simultaneously reconstructed with a pedicled anterolateral thigh flap transfer. The immunohistochemical study of the specimen revealed intraepidermal dysplastic glandular epithelial cells that were positive for CK7 and CK20 but negative for GCDFP15, suggesting that the Paget cells originated from internal malignancy. One year after the surgery, there was no recurrence of the cancer and no evidence of other malignancy. This case showed a rare presentation of secondary extramammary Paget disease in the peristomal skin of the ileal conduit. A pedicled perforator flap transfer was successfully used to immediately reconstruct a large peristomal skin defect after wide local excision.